Genesis of economic inequality in Ukraine in the context of its systemic consequences - Kovalenko, Mykola; Ziuz, Dmytro (Theory and Practice of Public Administration, 2026)
The article explores the genesis of economic inequality in Ukraine and its systemic consequences amidst contemporary macroeconomic and geopolitical shifts. Particular attention is paid to the fact that wealth stratification has evolved from a purely financial issue into an existential obstacle to sustainable socio-economic development and the preservation of societal integrity. It has been demonstrated that domestic inequality has deep structural roots and is not merely a consequence of objective market processes, but rather a result of the entrenchment of clan-oligarchic capitalism and the institutionalization of political rent extraction mechanisms. The methodological framework of the study is based on a systemic-institutional approach combined with historical-logical, statistical, and comparative methods, which allowed for viewing inequality as a logical consequence of defects in state policy and profound deformations in the public administration system. The empirical and informational basis of the research includes macroeconomic reviews and analytical reports from the World Bank (notably the Macro Poverty Outlook), Credit Suisse, as well as global studies by Oxfam, the IMF, and the Organization for Economic Co-operation and Development (OECD). The article provides a detailed periodization of domestic wealth stratification, structured into three key stages: the transformational crisis with primary capital accumulation (1991–1999), the period of oligarchic institutionalization (2000–2021), and the stage of acute economic inequality under martial law (2022–present). It is shown that the model of national asset distribution formed in Ukraine effectively blocks 99.8% of the adult population from efficient capital formation processes, thereby perpetuating socio-economic stagnation. The key result of the study is the identification of qualitatively new deformations of the social structure during the full-scale war. In particular, the transformation of classical income inequality into an acute polarization by real consumption level has been established, accompanied by an increase in poverty to 38% and a critical rise in the Gini coefficient to 0,50 in 2025. Factors contributing to the deepening of disparities are analyzed, including the intensification of sectoral imbalances and the disproportionate expansion of the shadow labor market, which most severely affects the most vulnerable segments of the population. It is emphasized that excessive stratification erodes public trust in the state, exacerbates legal nihilism, devalues integrity, and acts as a catalyst for demographic depression. Based on the analysis, the necessity for a radical change in the public administration strategy regarding the minimization of economic inequality is substantiated. The inefficiency of fragmented social benefit policies is highlighted, and the need for a transition to a mobilization development model and comprehensive structural reforms is argued. It is concluded that overcoming the destructive consequences of wealth polarization requires a fundamental transformation of the oligarchic governance model, expanding citizens’ access to productive resources, and active de-offshorization and formalization of the economy to establish institutional justice as an integral basis for a human-centric model of sustainable socio-economic development.